2019
DOI: 10.1177/2053369119830822
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endometrial assessment in women with unscheduled bleeding on hormone replacement therapy

Abstract: This study correlates the transvaginal ultrasound findings with histopathology results in women who present with unscheduled bleeding on hormone replacement therapy. Study design: Retrospective analysis of 469 consecutive cases with unscheduled bleeding on hormone replacement therapy (203 patients on sequential hormone replacement therapy (seq-HRT) and 266 patients on continuous combined hormone replacement therapy (con-HRT)). Main outcome measures: Outcomes of endometrial assessment in women with unscheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…6 In women on HRT, the risk has been estimated to be 1–2% as reported in previous studies. 2 , 5 The Million Women Study 13 reported a reduced risk of endometrial cancer in those on con-HRT, and no difference in those on seq-HRT as compared to women on no HRT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 In women on HRT, the risk has been estimated to be 1–2% as reported in previous studies. 2 , 5 The Million Women Study 13 reported a reduced risk of endometrial cancer in those on con-HRT, and no difference in those on seq-HRT as compared to women on no HRT.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with abnormal TVUS results (EMT ≥5 mm or polyps), results in our recent retrospective study revealed that the risk of atypical hyperplasia/endometrial cancer was low (2% and 1% for seq-HRT versus con-HRT). 5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations